Onrechtmatige Daad Notary In The Division Of Joint Property In The Cirebon District Court Decision Number 83/Pdt.G/2022/Pn Cbn - Amelia Frida Santi, Eva; Jamin, Mohammad; Mayastuti, Anti (CV. Inara, 2024)
This research aims to identify the causes of onrechtmatige daad Notary in the division of joint property in the decision of the Cirebon District Court number 83/Pdt.G/2022/PN Cbn. This research is a type of doctrinal legal research or normative legal research, with a statute approach and case approach. The sources of legal materials in this research are primary legal materials and secondary legal materials. The technique of collecting legal materials using literature studies and analyzed using the syllogism method using a deductive mindset. The results showed that the causes of Notary irregularities in the making of the deed of division of joint property in the decision of the Cirebon District Court number 83/Pdt.G/2022/PN Cbn, are: a) the absence of good faith from Defendant I and Defendant II (Notary), namely Defendant II (Notary) assisted Defendant I in making the Deed of Separation of Joint property number 66 dated January 26, 2016 without the knowledge, without meeting, without signatures, fingerprints and without explanation from the Plaintiff, the Notary violated Article 16 paragraph (1) letter a, letter b and letter c, Article 44 paragraph (1) b) Defendant II (Notary) did not read the deed in front of the Plaintiff, the Notary violated Article 16 paragraph (1) letter l. Defendant II (Notary) also violated Article 3 paragraph (1) of the Notary Code of Ethics. Defendant II (Notary) committed an act against the law (onrechtmatige daad) Article 1365 of the Civil Code, Defendant II (Notary) is subject to civil liability. Defendant I and Defendant I (Notary) are jointly and severally liable in paying immaterial damages to the Plaintiff, paying court costs and dwangsom fees. Sanctions on the deed made by the Notary become invalid and not legally binding, so that it is declared null and void.